The degree of commitment of physics teachers in Tabuk region to specialized professional standards - Al-Balawi, Murad Salem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the degree of commitment of physics teachers in Tabuk region to the specialized professional standards, and to achieve the objectives of the study, the researcher used the quantitative and qualitative approach and the tool was represented in the observation card and the semi-standardized interview guide based on a list of specific questions, which were applied to a sample of (17) teachers from the teachers Physics, and (4) teachers were selected to know the obstacles to physics teachers ’adherence to standards by conducting a semi-standardized interview. The results of the study showed: The degree of physics teachers’ commitment to the specialized professional standards of the standards obtained an overall average of (3.55) and a large degree. At the level of standards, the results showed a variation in the degree of commitment of physics teachers to specialized professional standards, as it ranged between very large and few, where (3) standards obtained a very large degree of commitment, while (6) standards obtained a large degree. of commitment and (7) standards came Medium commitment degree, low commitment degree one criterion.- As for the obstacles to physics teachers ’adherence to specialized professional standards, they were represented in: the weakness of the training programs provided to teachers, the lack of equipped laboratories, the weakness of the proportionality of the size of the scientific material with the classes allocated to it, the increase in the academic burden on the teacher. And the problem of rented buildings, and in light of the results of the study, the researcher presented a number of recommendations and proposals to improve the level of physics teachers ’adherence to specialized professional standards in the Tabuk region and the whole Kingdom.
Keywords: biology teacher; occupational standards; Tabuk region